2004
DOI: 10.1002/j.2158-1592.2004.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking Strategy, Structure, Process, and Performance in Integrated Logistics

Abstract: Supply chain management can create value by synchronizing logistical activities among participants to reduce costs associated with duplication of effort and positioning the entire supply chain to better serve key customers (Bowersox, Closs, and Stank 1999;Stank, Keller, and Closs 2001). Cost effective and hard to replicate logistical capabilities involve a high degree of operational integration within the firm to link procurement, the inbound movement of raw materials, manufacturing, delivery of products and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
157
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 18 publications
1
157
0
10
Order By: Relevance
“…Then, the correlation between SCI and OP in Figure 3a shows a slightly negative correlation. Many extant literatures (Rodrigues et al 2004;Cousins and Menguc 2006) have also shown findings in a similar vein that SCI does not appear to help much when the supply chain is under a highly volatile market place.…”
Section: Hierarchical Regression Results and Comparisonmentioning
confidence: 88%
See 1 more Smart Citation
“…Then, the correlation between SCI and OP in Figure 3a shows a slightly negative correlation. Many extant literatures (Rodrigues et al 2004;Cousins and Menguc 2006) have also shown findings in a similar vein that SCI does not appear to help much when the supply chain is under a highly volatile market place.…”
Section: Hierarchical Regression Results and Comparisonmentioning
confidence: 88%
“…Then, the correlation between SCI and OP in Figure 3a shows a slightly negative correlation. Many extant literatures (Rodrigues et al 2004; Cousins and Menguc 2006) have also shown findings in a similar vein that SCI does not appear to help much when the supply chain is under a highly volatile market place.Researchers in the area of agile supply chain also echoed their findings in a similar wavelength (Zhang 2011;Vazquez-Bustelo et al 2007). Essentially an agile supply chain prefers the management approach through virtual net-work rather than vertical integration (Agarwal et al 2006).…”
mentioning
confidence: 88%
“…For instance, Zahra & Nielsen (1998) used external integration as a moderator between manufacturing capabilities and technology commercialization. The literature highlights the positive association between integration and firm's performance (Rodrigues et al, 2004;Frohlich & Westbrook, 2001;Stank et al, 2001). External integration indicates the higher level of supply chain management and is positively related to business operational performance (Flynn et al, 2010;Stevens, 1990Stevens, , 1989.The interactions with outside parties have helped organisations to gain super business performance by giving immediate responses to the needs of customers (Frohlich & Westbrook, 2001).…”
Section: Resource Dependence Theory (Rdt) and External Integrationmentioning
confidence: 99%
“…When external involvement in the creation of customer service is incorporated with internal administration and technological innovation, high performance in supply chains tends to be created and sustained (Rodrigues, Stank & Lynch, 2004;Stank, Keller & Daugherty, 2001). More importantly, service innovation leading to business success can be achieved through the involvement of external customers in every order fulfillment process.…”
Section: Hypothesis 2: Market Orientation Positively Relates To Servimentioning
confidence: 99%